Implementation of The Internal Quality Assurance System in Improving School Quality - Agus Idris; Sutaryat Trisnamansyah; Iim Wasliman (Munaddhomah: Jurnal Manajemen Pendidikan Islam, 2022)
The Internal Quality Assurance System at SMP Darul Falah and SMP Negeri 02 Cililin has not been implemented optimally. school quality. The general objective of this study is to describe the implementation of school internal quality assurance in improving school quality and its specific objectives are to describe 1) quality mapping, 2) compilation of quality compliance plans, 3) implementation of quality compliance, 4) quality evaluation. 5) Determination of Quality Standards 6) Results of Quality Implementation 7) Obstacles in implementing SPMI. The implementation of SPMI itself according to Dirjendikdasmen (2016: 5) has the aim of ensuring that all elements, namely organization, policies, and processes related to educational units run by established standards to ensure the creation of a quality culture. This research procedure uses a qualitative approach with a case study method. The results of this study, in general, are that schools have implemented the SPMI implementation in improving the quality of schools in particular, namely: (1) Mapping, by carrying out school self-evaluation and school report cards. (2) Planning, schools carry out planning by the planning reference and format. (3) Implementation, the school has implemented SPMI starting at the initial stage, the core stage, and the final stage. (4) The school has carried out the SPMI evaluation by the monev team for each activity. (5) The school has developed a quality strategy for SPMI by the team using the formulation format, (6) The school has shown optimal learning outcomes through the application of SPMI with the satisfaction of various parties, (7) The school has resolved every problem with the right solution application of SPMI. The implementation of SPMI in schools is very helpful in improving the quality of the school, both academically and non-academically.